Prospecção de substâncias com potencial antioxidante em cultivares de Mangifera indica Linn: identificação e quantificação de compostos fenólicos - Barreto, Jacqueline do Carmo (2007)
Mango (Mangifera indica L.) belongs to the Anacardiaceae family, order Rutales and is one of the most important tropical fruits marketed in the world. This work describes the quantitation, identification and investigation of the antioxidant potential of phenolic compounds in methanol extracts of barks, peels, seeds and leaves (old and young) of sixteen cultivars of Mangifera indica Linn. [...]